Ontology mapping for querying heterogeneous information sources - Benslimane, Sidi Mohamed; Merazi, Afaf; Malki, Mimoun; Bensaber, Djamel Amar (INFOCOMP Journal of Computer Science, 2008)
Ontology mapping is becoming a crucial aspect in providing the background knowledge required for solving heterogeneity problems between semantically described data sources, and accessing distributed information repositories. Developing such ontology mapping has been a core issue of recent ontology research. In this paper we present a three-layer framework to (semi-)automatically discovering and using ontology mapping. We show how such resulting mapping is used for resolving semantic interrogation tasks, and enabling runtime semantic interoperability across heterogeneous information systems using semantic web technologies.